The employment market for librarians and information professionals in the top 500 corporations in Metro Manila - Calimag, Delia B. (1997)
A study about the employment market for librarians and information professionals (LIPs) in the top 500 corporations in Metro Manila was conducted to fulfill a three-fold mission: 1) to determine whether the job opportunities for LIPs in the corporate world of work; 2) to ascertain the skills, educational and personal qualifications required by the employers; and 3) to determine in which corporate units/functions and in what types of business the professional services and expertise of LIPs are needed most.